Eosinophilic dermatitis with edema (Wells'-like syndrome) possibly triggered by cooked fish in a dog - GIANNOULOPOULOS (Γ.Δ. ΓΙΑΝΝΟΥΛΟΠΟΥΛΟΣ), G. D.; FARMAKI (Ρ. ΦΑΡΜΑΚΗ), R.; KOUTINAS (Χ.Κ. ΚΟΥΤΙΝΑΣ), Ch. K.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
A 2-year old intact female mongrel dog was admitted with multifocal skin lesions appearing suddenly and extending symmetrically over most of the body. The dog was living indoors and one day before the admission it had consumed cooked fish. Neither medication, nor vaccination had been given to the dog, at least during the last 3 months. Physical examination revealed only non-pruritic and non-painful macules, papules and plaques that were distributed mainly over the head, pinnae, neck and thorax. The lesions were annular, aeriform or serpiginous with a tendency to coalesce. Skin histopathology (H-E) revealed a superficial dermal edema, post-capillary venule congestion and perivascular to interstitial eosinophilic dermatitis as the main pattern. The dog was initially placed on oral vitamin E, sulphasalazine and doxycycline, but to no avail. As soon as the diagnosis of eosinophilic dermatitis with edema was confirmed by histopathology, the former treatment stopped and oral prednisolone was given for two months during which there was a remarkable improvement of skin lesions and complete disappearance with no relapse. The cooked fish, consumed by the dog the night before the incident, was assumed to be the cause of the acute eosinophilic hypersensitivity reaction.